Antiviral and apoptosis modulating effect of methylenebisphosphonic acids - K, Naumenko; S, Zagorodnya; A, Golovan; V, Kovtyn (JOURNAL OF ADVANCES IN BIOLOGY, 2016)
The research of the molecular and genetic characteristics of Epstein-Barr virus are going for years and its ability to develop lymphoproliferative diseases. However, the search for effective antiviral and anticancer drugs remains relevant today. The aim was to investigate the biological properties methylenebisphosphonic acids (10s20-22), including cytotoxicity, apoptosis stimulating and antiviral activity. For this we used MTT-metod, PCR and flow cytometry. Also bioinformatic analysis was conducted using compounds PASS. It was shown 10s-20 compound effectively inhibits the replication of EBV in low concentrations. Compound 10c-21 showed a significant effect on apoptosis stimulating B95-8 cells. Data analysis showed prediction that this class of compounds may be a substrate for cytochrome C (CYP2H), which in turn may indicate the involvement of mitochondrial ways of inducing apoptosis. The data indicate that the group methylenebisphosphonic acids are perspective for further research